2014
DOI: 10.1016/j.nicl.2014.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Neuroimaging essentials in essential tremor: A systematic review

Abstract: BackgroundEssential tremor is regarded to be a disease of the central nervous system. Neuroimaging is a rapidly growing field with potential benefits to both diagnostics and research. The exact role of imaging techniques with respect to essential tremor in research and clinical practice is not clear. A systematic review of the different imaging techniques in essential tremor is lacking in the literature.MethodsWe performed a systematic literature search combining the terms essential tremor and familial tremor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
80
1
9

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(105 citation statements)
references
References 115 publications
1
80
1
9
Order By: Relevance
“…In a DTI study in WC, FA values were reported to be increased bilaterally in the white matter of the posterior limb of the internal capsule and adjacent structures in the patients compared to the controls. Abnormalities in DTI indices of the cerebellar peduncles and red nucleus have been reported in patients with ET [26]. Comparing our results with those reported in WC and ET, it appears that PWT is a separate entity with a different pathophysiology.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In a DTI study in WC, FA values were reported to be increased bilaterally in the white matter of the posterior limb of the internal capsule and adjacent structures in the patients compared to the controls. Abnormalities in DTI indices of the cerebellar peduncles and red nucleus have been reported in patients with ET [26]. Comparing our results with those reported in WC and ET, it appears that PWT is a separate entity with a different pathophysiology.…”
Section: Discussionsupporting
confidence: 80%
“…VBM has also been used to understand the pattern of gray matter changes in patients with ET [11][12][13]. Sharifi et al [26] in a latest review on neuroimaging in ET have highlighted six VBM studies in ET giving different results with predominant atrophy in some parts of cerebellum and cerebrum. The anterior lobe of the cerebellum has been reported to be atrophied in patients with ET [11], which is similar to our finding in patients with PWT.…”
Section: Discussionmentioning
confidence: 99%
“…The complexity of ET‐related pathology was supported by findings of cerebellar abnormalities and widespread brain neuro‐degeneration (Louis, 2014b, 2014c). The cerebello‐thalamo‐cortical network (Sharifi, Nederveen, Booij, & van Rootselaar, 2014) (cerebello‐thalamo‐cortical [CTC], also known as “tremor network”) has been proposed to play a substantial role in ET. In CTC network, the inferior olive nuclei project, via climbing fibers, to Purkinje cells in the contralateral cerebellar cortex, which send GABAergic inhibitory projections to the dentate and other deep cerebellar nuclei that in turn project to cortical brain areas via thalamic projections and to the red nucleus (Sharifi et al., 2014).…”
Section: Introductionmentioning
confidence: 99%
“…There are few proton MRS studies on the cerebellum and thalamus regions, which are thought to be mainly affected in the pathophysiology of ET (20). Louise et al (7) compared the cerebellar cortex, white matter, vermis, thalamus and basal ganglia of 16 ET patients and 11 healthy subjects using H-1 MRS examination and they found that the mean cerebellar cortex total creatine (tCR) NAA/tCR values of patients with ET were significantly lower than the control group.…”
Section: Discussionmentioning
confidence: 99%